THE INFLUENCE OF TAX KNOWLEDGE, TAX SERVICE QUALITY, AND TAX SANCTIONS ON INDIVIDUAL TAXPAYER COMPLIANCE - Ida Bagus Nyoman Rai Puja Krisnanda; I Ketut Jati (Adisam Publisher, 2025)
The significant contribution of taxes to the state budget (APBN) encourages the government, particularly the Directorate General of Taxes (DGT), to identify and enhance tax revenue potential. A tax ratio of 10.9 percent in 2021 places Indonesia below the Asia-Pacific average of 19.8 percent. In an effort to improve tax revenue, the government has implemented reforms aimed at increasing taxpayer compliance. This study uses a non-probability sampling method with an incidental sampling technique. The research was conducted at the West Denpasar Primary Tax Office (KPP Pratama Denpasar Barat), with 100 individual taxpayers selected based on the Slovin formula. The test results show that higher levels of tax knowledge, service quality, and strict tax sanctions are associated with increased individual taxpayer compliance. These findings are in line with the theory of planned behavior. It is recommended that KPP Pratama Denpasar Barat enhance the dissemination of applicable tax regulations and systems. Future researchers are advised to increase the sample size by expanding the research area and including objects beyond individual taxpayers.